Chinese discourses on the peasant, 1900-1949 - Han, Xiaorong, 1963- (SUNY series in Chinese philosophy and culture., 2005)
"Xiaorong Han explores how Chinese intellectuals envisioned the peasantry and its role in changing society during the first half of the twentieth century. Politically motivated intellectuals, both Communist and non-Communist, believed that rural peasants and their villages would be at the heart of change during this long period of national crisis. Nevertheless, intellectuals saw themselves as the true shapers of change who would transform and use the peasantry. Han uses intellectuals' writings to provide a comprehensive look at their views of the peasantry